Enhancing poultry health and productivity through the liver-gut axis with integrated nutritional and immunological approaches: a mini-review - Amevor, Felix Kwame; Uyanga, Victoria Anthony; Wu, Liuting; Xu, Dan; Shu, Gang; Wang, Yingjie; Zhao, Xiaoling (Frontiers in Physiology, 2025)
The liver-gut axis plays a central role in maintaining the health and productivity of poultry. In addition, the liver-gut axis serves as a key regulator of digestion, metabolism, immunity, and detoxification. The gut, with its diverse microbiota, is the primary site for nutrient absorption and immune modulation, while the liver metabolizes nutrients, detoxifies harmful substances, and acts as a frontline defense against pathogens translocated from the gut. Disruptions in this interconnected system, including gut dysbiosis or liver inflammation, can lead to compromised immunity and reduced productivity. This mini-review explores integrated nutritional and immunological strategies aimed at optimizing the liver-gut axis to enhance poultry performance. Nutritional interventions, such as the use of flavonoids, vitamins, amino acids, micronutrients, probiotics, prebiotics, and synbiotics, have demonstrated their potential to support liver and gut health. Dietary components such as phytogenic additives, fiber, and fatty acids further contribute to immune modulation and systemic health. Immunological approaches, such as beta-glucans and in ovo stimulation, and molecular approaches, including advanced genetic techniques, offer additional avenues for improving disease resistance and organ function. Despite notable advancements, challenges including antibiotic resistance, environmental stressors, and implementation costs persist. Emerging technologies like metagenomics, metabolomics, and precision breeding offer innovative solutions to enhance liver-gut interactions. This review underscores recent advancements in understanding the liver-gut axis and calls for holistic strategies to improve sustainable poultry production. Future research should integrate these approaches to enhance resilience, productivity, and sustainability in the poultry industry.